Photochemical pathways in nucleobases measured with an X-ray FEL. (1st April 2019) - Wolf, Thomas J. A.; Gühr, Markus
Abstract : The conversion of light energy into other molecular energetic degrees of freedom is often dominated by ultrafast, non-adiabatic processes. Femtosecond spectroscopy with optical pulses has helped in shaping our understanding of crucial processes in molecular energy-conversion. The advent of new, ultrashort and bright X-ray free electron laser sources opens the possibility to use X-ray-typical element and site sensitivity for ultrafast molecular research. We present two types of spectroscopy, ultrafast Auger and ultrafast X-ray absorption spectroscopy, and discuss their sensitivity to molecular processes. While Auger spectroscopy is able to monitor bond distance changes in the vicinity of an X-ray created core hole, near-edge absorption spectroscopy can deliver high-fidelity information on non-adiabatic transitions involving lone-pair orbitals. We demonstrate these features on the example of the UV-excited nucleobase thymine, investigated at the oxygen K-edge. We find a C–O bond elongation in the Auger data in addition to ππ* / nπ* non-adiabatic transition in X-ray near-edge absorption. We compare the results from both methods and draw a conclusive scenario of non-adiabatic molecular relaxation after UV excitation. This article is part of the theme issue 'Measurement of ultrafast electronic and structural dynamics with X-rays'.